2008
DOI: 10.1007/s10551-008-9747-7
|View full text |Cite
|
Sign up to set email alerts
|

The Duality of Crony Corruption in Economic Transition: Toward an Integrated Framework

Abstract: local corporatism, crony corruption, dual-track transition, formal–informal interplay, economic–political interplay, China,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 64 publications
(116 reference statements)
0
17
0
Order By: Relevance
“…Corruption can lead to low levels of generalized trust, as people are not willing to trust strangers (Li 2009). According to Rothstein and Stolle (2001), the behaviors of state officials give important signals to citizens about the moral standards of the society.…”
Section: The Roles Of Formal and Informal Institutions In Social Trusmentioning
confidence: 99%
See 1 more Smart Citation
“…Corruption can lead to low levels of generalized trust, as people are not willing to trust strangers (Li 2009). According to Rothstein and Stolle (2001), the behaviors of state officials give important signals to citizens about the moral standards of the society.…”
Section: The Roles Of Formal and Informal Institutions In Social Trusmentioning
confidence: 99%
“…The absence of generalized trust results in more reliance on particularized trust-trust between people from the same groups or networks in order to make social exchanges (Li 2009;Rothstein and Stolle 2001). In a study on trust and interfirm relationships in Vietnam, Nguyen et al (2005) found that mutual acquaintances facilitate the establishing of trust and relationships between two strangers.…”
Section: The Roles Of Formal and Informal Institutions In Social Trusmentioning
confidence: 99%
“…The autocrat typically co‐opts supporters through preferential economic privileges. Autocracies use their legal systems to create and preserve economic advantages for crony firms (Donaldson ; Li ). Autocracies can close down rival firms while depriving them of any recourse to independent courts or a free press.…”
Section: Autocratic Political Power Needs Cronyism and Opacitymentioning
confidence: 99%
“…We need a fine‐grained perspective to define corruption in nondemocratic societies, the more so when a country is in a transition process from a centrally‐led government to a market economy (Luo, ; Hodgson and Shuxia, ; Guerrero and Rodríguez‐Oreggia, ; Li, ). The word ‘corruption’ is used to mean different things in different countries and different global contexts (Bardhan, ; Collier, ; Kurer, ; Kwok and Tadesse, ).…”
Section: Theory and Hypothesesmentioning
confidence: 99%